Ernst-von-Glasersfeld-Archiv. Eröffnung - Inauguration - Hug, Theo; Schorner, Michael; Mitterer, Josef (innsbruck university press, 2013)
Ernst von Glasersfeld (1917-2010) was a scholar in the fields of philosophy and communications who became one of the most influential thinkers of the present through developing the theory of radical constructivism. This volume documents the official opening of a new archive at the University of Innsbruck which makes the literary estate of Ernst von Glasersfeld accessible to researchers. The collection includes the inaugural remarks, an overview of the estate, a series of personal notes remembering the scientist and man, as well as the initial two in a series of lectures addressing his extensive work. - Der Philosoph und Kommunikationswissenschaftler Ernst von Glasersfeld (1917-2010) wurde durch die Entwicklung der Theorie des Radikalen Konstruktivismus zu einem der einflussreichsten Denker der Gegenwart. Der vorliegende Band dokumentiert die offizielle Eröffnung eines neuen Archivs an der Universität Innsbruck, in dem der Nachlass von Ernst von Glasersfeld für die Forschung zugänglich gemacht wird. Neben den Grußworten, einem Überblick über den Nachlass, sowie einer Reihe von Personal Notes, die an den Wissenschaftler und Menschen erinnern, sind hier auch die beiden ersten Beiträge einer Vortragsreihe abgedruckt, die sich seinem umfangreichen Werk widmen.